SERVICE EXCELLENT RUMAH MAKAN PADANG DALAM PERSPEKTIF WISATA ISLAMI - Wardi, Yunia; Abror, Abror; Trinanda, Okki (Universitas Pendidikan Ganesha, 2019)
Padang Restaurant is one of the ethnic restaurants in Indonesia from Minangkabau. The existence and